Google Form Creation Training and Legal Awareness Outreach in Neglasari Village - Lilis Emalia; Yane Mayasari; Rini Susilawati; Fitri Nurlaela; Yulia Ambarsari; Bisma Indrawan (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2025)
The community service initiative in Neglasari Village seeks to improve the digital competencies of women participating in the Family Empowerment and Welfare program and local village officials through training on using Google Forms. This program offers a practical understanding of a digital tool for data collection and information-driven decision-making. Furthermore, initiatives are undertaken to emphasize the significance of legal knowledge in everyday life, thereby enhancing participants' comprehension of their rights and responsibilities. The activity's results indicate that the participatory, technology-driven approach enhances participants' digital competencies and elevates legal awareness. Active discussion sessions enhance participants' engagement and motivation to implement their newly acquired information in social circumstances. We advocate frequent conduct of analogous training sessions, with content modified to meet the requirements of the Family Empowerment and Welfare program and local village officials.